Utilization of Automatic Exchange of Information (AEoI) in Efforts to Increase Taxpayer Compliance - Simanjuntak, Patrick Naomi Maysias; Sari, Dahlia (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
This research aims to evaluate the effectiveness of using Automatic Exchange of Information (AEOI) data in increasing individual taxpayer compliance, especially regarding mandatory personal income tax at KPP Y. This research uses a case study approach and qualitative methods. Context evaluation shows that the use of AEOI data in KPP Y provides a good understanding of WP compliance issues and the purpose of using AEOI data. Input evaluation shows that resource availability, technical understanding, and responsibility related to AEOI implementation have been achieved well. Process evaluation indicates that implementation is according to plan, handling obstacles with the right approach, and a positive response from WP. This research has a positive impact on the use of AEOI data in increasing taxpayer compliance, especially regarding the Voluntary Disclosure Program (PPS). The main innovation lies in recommendations for routine derivation of AEOI data, verification of data from other countries, and improvement of data comprehensiveness.